Ultrathin antimony oxide nanobelt as well as preparation method and application thereof

By using hydrothermal method to prepare ultra-thin antimony oxide nanoribbons under normal pressure, the problems of high cost, polluting the environment and poor sample quality in the preparation process in the prior art are solved, and efficient and environmentally friendly nanoribbon preparation is achieved. Excellent electrochemical properties are shown in sodium ion batteries.

CN119461479AActive Publication Date: 2025-02-18ZHONGBEI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411687104.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-18
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

In the prior art, antimony oxide (Sb2O3) nanoribbons require high temperatures and surfactants during the preparation process, resulting in high costs, polluted environment and relatively poor sample quality, and their cycling stability and charge and discharge in sodium ion batteries. Capacity is limited.

Method used

Ultrathin antimony oxide nanoribbons were prepared under normal pressure by hydrothermal method, high-purity antimony powder was used as raw material, and thickness was prepared by dot ultrasonic treatment and hydrothermal synthesis reaction, combined with water bath ultrasonic peeling, centrifugal purification and freeze-drying steps. Ultra-thin Sb2O3 nanoribbons less than 40 nm without the addition of surfactant.

Benefits of technology

It realizes efficient preparation of ultra-thin Sb2O3 nanoribbons, with high material quality, good dispersion, high yield and high oxidation, etc., which reduces the preparation cost, avoids pollution of the environment, and shows good charging and discharge in the anode material of sodium ion battery Capacity, cycle stability and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461479A_ABST
    Figure CN119461479A_ABST
Patent Text Reader

Abstract

The invention relates to the field of new energy industry, in particular to an ultrathin antimony oxide nanobelt and a preparation method and application thereof. Firstly, high-strength point ultrasound is adopted, and the size of antimony powder particles is reduced to 20 nm or below by controlling ultrasonic conditions; secondly, a mild hydrothermal synthesis method is adopted, and aggregate of the Sb2O3 nanobelt is prepared by controlling the hydrothermal temperature; and the last step comprises the operations of stripping, separation and purification, freeze drying and the like to obtain a powder material of the ultrathin Sb2O3 nanobelt. The Sb2O3 nanobelt prepared by the method has the characteristics of high quality, good dispersity, high yield, high oxidation degree and the like, so that the technical defects of relatively poor sample quality, low yield and the like of the Sb2O3 nanobelt in the prior art are overcome. The Sb2O3 nanobelt-based sodium ion battery anode material prepared by the preparation method disclosed by the invention shows good charge-discharge capacity, cycling stability and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy industry, and in particular to an ultra-thin antimony oxide nanobelt and a preparation method and application thereof, and a high-efficiency sodium ion battery is prepared by using the antimony oxide nanobelt as an anode material. Background Art

[0002] Unlike lithium-ion batteries, graphite's inert properties for sodium storage limit its sodium storage capacity, which seriously restricts its application in sodium-ion batteries (SIBs) (Y. Wen, K. He, Y.Zhu, F. Han, Y. Xu, I. Matsuda, Y. Ishii, J. Cumings, C. Wang, Expandedgraphite as superior anode for sodium-ion batteries, Nature communications , 2014, 5(4033). Therefore, it is crucial to explore suitable anode materials to promote the commercialization of SIBs. Among the various reported SIBs anode materials, antimony oxide (Sb2O3) has been widely used due to its relatively low cost, environmental friendliness, and ultra-high sodiumization rate (13.5 nm∙s −1 ) and over 1100 mAh∙g based on conversion alloy mechanism −1The inherent high theoretical capacity and other advantages make it a competitive candidate material (Y. Zheng, Z. Zhang, W. Liu, Y. Wu, X. Fu, L. Li, J. Su, Y. Gao, Investigations on the Electrochemical and Mechanical Properties of Sb2O3 Nanobelts by In Situ Transmission Electron Microscopy, Small Methods, 2022, 6(3): e2101416; J. Fei, Y. Cui, J. Li, Z. Xu, J. Yang, R. Wang, Y.Cheng, J. Hang, A flexible Sb2O3 / carbon cloth composite as a free-standing high performance anode for sodium ion batteries, Chem. Commun., 2017, 53(98): 13165-13167.). However, similar to other metal oxides, the poor rate capability and cyclability of Sb2O3 due to volume expansion during the salting / desalting process greatly limits the practical application of Sb2O3-based anode materials (MV Reddy, GV Subba Rao, BV Chowdari, Metal oxides and oxysalts as anode materialsfor Li ion batteries, Chem. Rev., 2013, 113(7): 5364-5457.).

[0003] Considering the anisotropic properties of crystalline anode materials, the volume change observed during the cycle also exhibits anisotropic behavior. Therefore, designing low-dimensional crystalline materials is expected to be used to reduce the negative impact of volume expansion. For example, Lin et al. developed double-zigzag Sb2O3 microbelts with a width of 800 nm, a thickness of 250 nm, and a length of several microns for use as anode materials for sodium-ion batteries (Z. Li, D. Fang, W. Zhang, J. Tian, ​​S. Chen, J. Liang , N. Lin,Y. Qian, Revealing Quasi-1D Volume Expansion in Na- / K-Ion Battery Anodes: ACase Study of Sb2O3 Microbelts, CCS Chem., 2020, 2:1306-1315. The results show that when the current density is 0.05 A∙g −1 The discharge capacity of these microstrips after 50 cycles is 470 mAh∙g −1. In addition, the Sb2O3 microbelts undergo significant volume expansion along the

[100] direction perpendicular to the belt plane. Based on this inspiration, minimizing the thickness of the microbelts can effectively reduce the crystal plane in the

[100] direction and increase the specific surface area of ​​the active material. This strategy has important application potential in further improving the cycling stability and charge-discharge capacity of Sb2O3. However, there are currently limited reports on the preparation of Sb2O3 nanobelts, and the commonly used methods can be roughly divided into two categories. One category includes chemical vapor deposition (N. Pradeep, V.Chaitra, V. Uma, AN Grace, Antimony oxide nanobelts: synthesis by chemicalvapour deposition and its characterisation, Int. J. Nanotechnol., 2017, 14(9-11): 752-761.). The Sb2O3 nanobelts produced by this technology usually have high purity and excellent crystallinity, but they usually require temperatures exceeding 500 °C and have relatively low yields, making them unsuitable for large-scale applications. Other methods include hydrothermal methods using antimony salts or antimony powders as the main raw materials [L. Li, YX Zhang, XS Fang, TY Zhai, MYLiao, HQ Wang, GH Li, Y. Koide, Y. Bando, D. Golberg, Sb2O3 nanobeltnetworks for excellent visible-light-range photodetectors, Nanotechnology ,2011, 22(16): 165704; ZT Deng, D. Chen, FQ Tang, J. Ren, AJ Muscat,Synthesis and Purple-Blue Emission of Antimony Trioxide Single-CrystallineNanobelts with Elliptical Cross Section, Nano Res., 2009, 2(2): 151-160.]. Among them, the hydrothermal synthesis method that directly uses antimony powder as the antimony source is simpler and more efficient. However, these methods often require a large amount of surfactants, such as polyvinyl pyrrolidone (PVP), ethylenediamine (EDA), hexadecyltrimethylammonium bromide (CTAB), etc., which not only increases the production cost; but also the residual chemicals will have some unpredictable effects on the inherent properties of the material. Therefore, achieving efficient preparation of ultrathin Sb2O3 nanobelts remains a major challenge. Summary of the invention

[0004] The present invention overcomes the deficiencies of the prior art and provides a method for preparing ultrathin antimony oxide nanobelts. A simple and efficient hydrothermal method is used to prepare ultrathin Sb2O3 nanobelts in an orthorhombic phase. The notable feature of the present invention is that high-purity antimony powder is used as the raw material, the entire synthesis process is carried out in deionized water under normal pressure, and no surfactant or other chemical reagents need to be added. The preparation method of the present invention is green and environmentally friendly, simple and easy to operate, and can greatly reduce the preparation cost. The prepared Sb2O3 nanobelts have the characteristics of high quality, ultrathinness, good dispersibility, high yield, and high degree of oxidation, so as to overcome the technical defects of the prior art methods, such as the relatively poor quality of the Sb2O3 nanobelt samples, the high cost of the preparation method, and the environmental pollution.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing ultrathin antimony oxide nanobelts, comprising the following steps: (1) taking commercial high-purity antimony powder and placing it in deionized water to prepare an antimony aqueous solution, and then subjecting the antimony aqueous solution to point ultrasonic treatment in an ice bath to prepare an aqueous solution containing small-sized antimony particles or antimony quantum dots; (2) diluting the aqueous solution containing small-sized antimony particles or antimony quantum dots in step (1) with deionized water, and then performing a hydrothermal synthesis reaction under normal pressure and vigorous stirring to obtain an aqueous solution containing Sb2O3 nanobelt aggregates; (3) subjecting the aqueous solution containing Sb2O3 nanobelt aggregates in step (2) to water bath ultrasonic exfoliation to obtain an aqueous solution containing ultrathin Sb2O3 nanobelts; (4) The aqueous solution of the ultrathin Sb2O3 nanobelts in step (3) is separated and purified by a step-by-step centrifugation method, and then the separated and purified aqueous solution is freeze-dried to collect the powder material of the ultrathin Sb2O3 nanobelts.

[0006] As a further limitation of the technical solution of the present invention, in step (1), the mass volume ratio of the aqueous solution of antimony powder is 0.5-1.5 g / L; the step of point ultrasonication is: ultrasonication for 2-5 hours in an ice bath environment, the ultrasonic wave is output in the form of a pulse lasting 2 seconds every 4 seconds, and the ultrasonic power is 400-600 W, to obtain an aqueous solution containing antimony powder particles with a diameter of 3-20 nm.

[0007] As a further limitation of the technical solution of the present invention, it is characterized in that in step (1), the antimony powder is first ground by a ball mill, and after the grinding is completed, the antimony powder is dispersed in deionized water to obtain an aqueous solution containing small-sized antimony powder particles, and the grinding conditions are: using a zirconia grinding jar and ball milling balls, which are composed of grinding balls with a particle size of 5 mm and grinding balls with a particle size of 3 mm, and the number ratio of the two is 1:1, the ball mill speed is 900-1100 rpm, and the grinding is 30-60 min.

[0008] As a further limitation of the technical solution of the present invention, the mass volume ratio of the diluted aqueous solution containing small-sized antimony particles or antimony quantum dots in step (2) is 0.25-0.75 g / L; the conditions of the hydrothermal synthesis reaction are: hydrothermal temperature 60-90 ° C, reaction time 1-3 h.

[0009] As a further limitation of the technical solution of the present invention, the conditions for water bath ultrasonic stripping are: the water bath temperature is room temperature, the ultrasonic power is 100-200 W, and the ultrasonic time is 1-3 h.

[0010] As a further limitation of the technical solution of the present invention, the operation of stepwise centrifugation and freeze drying in step (4) is: S1, centrifuge the aqueous solution containing ultrathin Sb2O3 nanobelts at 3000 rpm for 5 min, and take the supernatant I; S2, centrifuging the supernatant I obtained in step S1 at 6000 rpm for 20 min to obtain precipitate I and supernatant II; S3. Re-dispersing the precipitate I obtained in step S2 in deionized water, and freeze-drying to obtain an ultra-thin Sb2O3 nanobelt powder material.

[0011] The present invention also provides an ultra-thin antimony oxide nanobelt obtained by the above preparation method.

[0012] As a further limitation of the technical solution of the present invention, the length of the Sb2O3 nanobelt exceeds 10 μm, the width is 170-500 nm, and the thickness is 30-40 nm.

[0013] In addition, the present invention also provides the use of the ultra-thin antimony oxide nanobelt in preparing anode materials for sodium ion batteries.

[0014] As a further limitation of the above application, the preparation method of the sodium ion battery anode material is: ultrathin Sb2O3 nanobelt powder material, conductive carbon black (Super P) and carboxymethyl cellulose are mixed in a mass ratio of 7:2:1, and deionized water is added to prepare it into a slurry, which is coated on a copper foil, and then the coated copper foil is dried in a vacuum oven at 80°C for 12 h, and then cut into electrode sheets with a diameter of 12 mm.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a novel and simple method for preparing ultrathin Sb2O3 nanobelts, which specifically comprises: using high-purity antimony powder as raw material, preparing ultrathin antimony oxide nanobelts with a thickness of less than 40 nm by a hydrothermal synthesis method in deionized water without adding any surfactant or other chemical reagents; The whole synthesis process can be roughly divided into three steps: first, high-intensity point ultrasound is used to control the ultrasound conditions to reduce the size of the antimony powder particles to less than 20 nm. This process can also be achieved by ball milling; second, a mild hydrothermal synthesis method is used to prepare the aggregates of Sb2O3 nanobelts by controlling the hydrothermal temperature; the last step includes: stripping, separation and purification, and freeze-drying, that is, the aqueous solution containing the aggregates of Sb2O3 nanobelts described in the second step is firstly subjected to water bath ultrasonic stripping at room temperature to obtain an aqueous solution containing ultrathin Sb2O3 nanobelts, and then centrifugally purified to obtain an aqueous solution of Sb2O3 nanobelts with a specific size and thickness, and then freeze-dried to collect the powder material of ultrathin Sb2O3 nanobelts.

[0016] The present invention uses high-purity antimony powder as raw material and utilizes a simple hydrothermal synthesis method in pure water to prepare ultrathin Sb2O3 nanobelts. The preparation method of the present invention is green and environmentally friendly, simple and easy to operate, and can greatly reduce the preparation cost. The prepared Sb2O3 nanobelts have the characteristics of high quality, good dispersibility, high yield, high oxidation degree, etc., thereby overcoming the technical defects of the prior art methods such as relatively poor quality and low yield of Sb2O3 nanobelt samples.

[0017] 3. The Sb2O3 nanobelt-based sodium ion battery anode material prepared by the present invention exhibits good charge and discharge capacity, cycle stability and rate performance. Specifically, in a standard CR2032 button cell, the Sb2O3 nanobelt-based anode exhibits good charge and discharge capacity, cycle stability and rate performance at 0.1A·g −1 At this current, after 150 cycles, its discharge capacity still retained 443.1 mAh g −1 In addition, at 2.0 A∙g −1 Under the condition of −1 The average reversible rate capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a schematic diagram and actual picture of the process for preparing Sb2O3 nanobelts according to Example 1 of the present invention.

[0019] Figure 2 (a) low-magnification TEM image and (b) high-resolution TEM image of the Sb quantum dot sample prepared in step (1) of Example 1 of the present invention.

[0020] Figure 3 (a) low-magnification SEM image and (b) high-resolution SEM image of the ultrathin Sb2O3 nanobelt sample prepared in step (4) of Example 1 of the present invention. Figure 4 (a) AFM image and corresponding (b) height image of the ultrathin Sb2O3 nanobelt sample prepared in step (4) of Example 1 of the present invention.

[0021] Figure 5 (a) XRD pattern and (b) Raman pattern of the ultrathin Sb2O3 nanobelt sample prepared in step (4) of Example 1 of the present invention.

[0022] Figure 6 (a) low-magnification TEM image and (b) high-resolution TEM image of the ultrathin Sb2O3 nanobelt sample prepared in step (4) of Example 1 of the present invention.

[0023] Figure 7 (a) Cycling performance and (b) rate performance of the ultrathin Sb2O3 nanobelt-based anode prepared in step (5) of Example 1 of the present invention. DETAILED DESCRIPTION

[0024] The present invention is further described below in conjunction with specific embodiments. Example 1

[0025] like Figure 1 As shown, a method for preparing ultrathin antimony oxide nanoribbons in pure water as a high-efficiency anode for sodium ion batteries comprises the following steps: (1) Take an appropriate amount of commercial high-purity antimony powder and place it in deionized water to prepare an antimony aqueous solution with a solubility of 1 g / L; then the antimony aqueous solution is subjected to point ultrasonic treatment. The specific steps are: ultrasonic treatment for 3 h in an ice bath environment, with the ultrasonic wave output in the form of a pulse lasting 2 seconds every 4 seconds and an ultrasonic power of 500 W, to obtain an aqueous solution containing antimony quantum dots with a diameter of about 5 nm, such as Figure 2 As shown; (2) diluting the aqueous solution containing antimony quantum dots of about 5 nm in size prepared in step (1) with deionized water to 0.5 g / L; then conducting a hydrothermal synthesis reaction under normal pressure and vigorous stirring, wherein the specific steps are as follows: the hydrothermal temperature is 80 °C and the reaction time is 2 h, thereby obtaining an aqueous solution containing Sb2O3 nanobelt aggregates; (3) subjecting the aqueous solution containing Sb2O3 nanobelt aggregates in step (2) to water bath ultrasonic exfoliation, wherein the specific operation is: the water bath temperature is room temperature, the ultrasonic power is 200 W, and the ultrasonic time is 2 h to obtain an aqueous solution containing ultrathin Sb2O3 nanobelts; (4) The aqueous solution of Sb2O3 nanobelts in step (3) is separated and purified by a stepwise centrifugation and freeze-drying method and a sample is collected. The specific operation is as follows: S1, centrifuge the aqueous solution containing Sb2O3 nanobelts at 3000 rpm for 5 min, and take the supernatant I; S2, centrifuging the supernatant I obtained in step S1 at 6000 rpm for 20 min to obtain precipitate I and supernatant II; S3. Re-dispersing the precipitate I obtained in step S2 in deionized water, and freeze-drying to obtain powdered ultra-thin Sb2O3 nanobelts.

[0026] (5) The powder material of the ultrathin Sb2O3 nanobelt in step (4) was used as the anode material of the sodium ion battery, and the sodium storage performance of the Sb2O3 nanobelt-based anode was tested in a standard CR2032 button battery. The specific operation was as follows: the powdered ultrathin Sb2O3 nanobelt, conductive carbon black (Super P) and carboxymethyl cellulose in step (4) were mixed in a mass ratio of 7:2:1, and an appropriate amount of deionized water was added to prepare a slurry to be coated on a copper foil. The coated copper foil was then dried in a vacuum oven at 80 °C for 12 h, and then cut into electrode sheets with a diameter of 12 mm. These electrode sheets were then used to assemble CR2032 button batteries, and their sodium storage performance was characterized. The cycling performance and rate performance of the Sb2O3 nanobelt-based anode are shown in Figure 2. Figure 7 As shown, specifically: Sb2O3 nanobelt-based anode at 0.1 A·g −1 At this current, after 150 cycles, its discharge capacity still retained 443.1 mAh g −1 In addition, at 2.0 A∙g −1 Under the condition of −1 The average reversible rate capacity. Example 2

[0027] The difference between this example and Example 1 is that the initial solubility of the antimony powder aqueous solution in step (1) is 1.5 g / L. The remaining steps and parameters are the same as those in Example 1. Example 3

[0028] The difference between this example and Example 1 is that the ultrasonic power in step (1) is 600 W and the ultrasonic time is 2 h. The remaining steps and parameters are the same as those in Example 1. Example 4

[0029] The difference between this example and Example 1 is that the hydrothermal temperature in step (2) is 90°C and the reaction time is 1 h. The remaining steps and parameters are the same as those in Example 1. Example 5

[0030] The difference between this example and Example 1 is that the hydrothermal temperature in step (2) is 60°C and the reaction time is 3 h. The remaining steps and parameters are the same as those in Example 1. Example 6

[0031] The difference between this example and Example 1 is that the ultrasonic power of water bath ultrasonic stripping in step (3) is 100 W and the ultrasonic time is 3 h. The remaining steps and parameters are the same as those in Example 1. Example 7

[0032] The difference between this example and Example 1 is that step (1) is completed by ball milling. The remaining steps and parameters are the same as those in Example 1.

[0033] Ball milling steps: Use zirconia grinding jars and ball milling balls, which consist of grinding balls with a particle size of 5 mm and grinding balls with a particle size of 3 mm, and the number ratio of the two is 1:1. The ball mill speed is 1100 rpm, and the grinding is carried out for 30 minutes. After grinding, it is dispersed in deionized water to obtain an aqueous solution containing small-sized antimony powder particles. The mass volume ratio of the aqueous solution is 0.5 g / L. Example 8

[0034] The difference between this example and Example 1 is that step (1) is completed by ball milling. The remaining steps and parameters are the same as those in Example 1.

[0035] Ball milling steps: Use zirconia grinding jars and ball milling balls, which consist of grinding balls with a particle size of 5 mm and grinding balls with a particle size of 3 mm, and the number ratio of the two is 1:1. The ball mill speed is 900 rpm and the grinding is performed for 60 min. After grinding, it is dispersed in deionized water to obtain an aqueous solution containing small-sized antimony powder particles. The mass volume ratio of the aqueous solution is 0.5 g / L.

[0036] Well-defined ultrathin Sb2O3 nanoribbons were successfully prepared in pure deionized water. Figure 2(a) and (b) SEM characterization of the sample after completing step (1). The results show that the size of the antimony powder is reduced to the size of quantum dots after point ultrasonic treatment.

[0037] Figure 3 This is the SEM of the ultra-thin Sb2O3 nanobelt sample in step (4). The results show that the length of the Sb2O3 nanobelt exceeds 10 μm and the width is 170-480 nm.

[0038] like Figure 4 As shown in Figure 2, the thickness of the ultrathin Sb2O3 nanobelt samples in step (4) was analyzed by AFM. The results showed that the thicknesses of the nanobelts with widths of 323.2 nm and 336.7 nm were 34.1 nm and 38.4 nm, respectively.

[0039] like Figure 5 As shown, the crystal structure of the ultra-thin Sb2O3 nanobelt sample in step (4) was further analyzed by XRD and Raman spectroscopy. The results show that the crystal structure of the Sb2O3 nanobelt sample at this time is mainly orthorhombic Sb2O3.

[0040] Figure 6 The TEM image of the ultrathin Sb2O3 nanobelt sample in step (4) shows that the Sb2O3 nanobelt sample exhibits a good nanobelt structure and has a (002) crystal plane belonging to the orthorhombic Sb2O3 system, further confirming that Figure 5 result.

[0041] like Figure 7 As shown in the figure, the sodium storage performance of the ultra-thin Sb2O3 nanobelt sample in step (4) was tested in a standard CR2032 button battery. The results show that the Sb2O3 nanobelt-based sodium ion battery anode material prepared by the present invention exhibits good charge and discharge capacity, cycle stability and rate performance. Specifically: The Sb2O3 nanobelt-based anode has a good charge and discharge capacity, cycle stability and rate performance at 0.1 A·g −1 At this current, after 150 cycles, its discharge capacity still retained 443.1 mAh g −1 In addition, at 2.0 A∙g −1 Under the condition of −1 The average reversible rate capacity.

[0042] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing ultrathin antimony oxide nanoribbons, characterized in that: The following steps are involved: (1) taking antimony powder and placing it in deionized water to prepare an antimony aqueous solution, and then subjecting the antimony aqueous solution to point ultrasonic treatment in an ice bath to prepare an aqueous solution containing small-sized antimony particles or antimony quantum dots; (2) diluting the aqueous solution containing small-sized antimony particles or antimony quantum dots in step (1) with deionized water, and then performing a hydrothermal synthesis reaction under normal pressure and vigorous stirring to obtain an aqueous solution containing Sb2O3 nanobelt aggregates; (3) subjecting the aqueous solution containing Sb2O3 nanobelt aggregates in step (2) to water bath ultrasonic exfoliation to obtain an aqueous solution containing ultrathin Sb2O3 nanobelts; (4) The aqueous solution of the ultrathin Sb2O3 nanobelts in step (3) is separated and purified by a step-by-step centrifugation method, and then the separated and purified aqueous solution is freeze-dried to collect the powder material of the ultrathin Sb2O3 nanobelts.

2. The method for preparing an ultrathin antimony oxide nanoribbon according to claim 1, characterized in that: In step (1), the mass volume ratio of the antimony powder aqueous solution is 0.5-1.5 g / L; the point ultrasonic step is: ultrasonicate for 2-5 hours in an ice bath environment, the ultrasonic wave is output in the form of a pulse lasting 2 seconds every 4 seconds, and the ultrasonic power is 400-600 W, to obtain an aqueous solution containing antimony powder particles with a diameter of 3-20 nm.

3. The method for preparing an ultrathin antimony oxide nanoribbon according to claim 2, characterized in that: In step (1), the antimony powder is first ground using a ball mill. After grinding, the antimony powder is dispersed in deionized water to obtain an aqueous solution containing small-sized antimony powder particles. The grinding conditions are: a zirconia grinding jar and ball milling balls are used, which are composed of grinding balls with a particle size of 5 mm and grinding balls with a particle size of 3 mm, and the number ratio of the two is 1:

1. The ball mill speed is 900-1100 rpm, and the grinding is 30-60 min.

4. The method for preparing an ultrathin antimony oxide nanoribbon according to claim 1, characterized in that: The mass volume ratio of the diluted aqueous solution containing small-sized antimony particles or antimony quantum dots in step (2) is 0.25-0.75 g / L; the conditions of the hydrothermal synthesis reaction are: hydrothermal temperature 60-90 ° C, reaction time 1-3 h.

5. The method for preparing an ultrathin antimony oxide nanoribbon according to claim 1, characterized in that: The conditions for water bath ultrasonic stripping are: water bath temperature is room temperature, ultrasonic power is 100-200 W, and ultrasonic time is 1-3 h.

6. The method for preparing an ultrathin antimony oxide nanoribbon according to claim 1, characterized in that: The operation of stepwise centrifugation and freeze drying in step (4) is as follows: S1, centrifuge the aqueous solution containing ultrathin Sb2O3 nanobelts at 3000 rpm for 5 min, and take the supernatant I; S2, centrifuging the supernatant I obtained in step S1 at 6000 rpm for 20 min to obtain precipitate I and supernatant II; S3. Re-dispersing the precipitate I obtained in step S2 in deionized water, and freeze-drying to obtain an ultra-thin Sb2O3 nanobelt powder material.

7. An ultrathin antimony oxide nanobelt obtained by the preparation method according to any one of claims 1 to 6.

8. The ultrathin antimony oxide nanoribbon according to claim 7, characterized in that: The Sb2O3 nanoribbons have a length of more than 10 μm, a width of 170-500 nm, and a thickness of 30-40 nm.

9. Use of the ultrathin antimony oxide nanoribbon according to claim 8 in preparing anode materials for sodium ion batteries.

10. The application according to claim 9, characterized in that: The preparation method of the sodium ion battery anode material is as follows: ultra-thin Sb2O3 nanobelt powder material, conductive carbon black and carboxymethyl cellulose are mixed in a mass ratio of 7:2:1, and deionized water is added to prepare it into a slurry and coated on a copper foil, and then the coated copper foil is dried in a vacuum oven at 80 °C for 12 h, and then cut into electrode sheets with a diameter of 12 mm.

Citation Information

Patent Citations

  • Method for preparing ordered antimony-based oxide self-assembled nanometer cluster and nano-wire materials

    CN101519225A

  • Method for efficiently and controllably preparing novel two-dimensional antimonene oxide in pure water by using liquid-phase ultrasonic stripping technology

    CN117164006A

  • Method and system for preparing superfine antimony oxide through ultrasonic energizing-micro-liquid oxidation

    CN118062889A